(untitled) (Journal of Economics and Sustainability, 2024)
Various technologies and e-learning tools have been adopted in the teaching and learning process. This transformation has not only affected the teachers and students, but also parents, school management and other stakeholders. This research aims to investigate Malaysian parents’ awareness, attitudes, and social influence and willingness in shaping their own perception toward the adoption of augmented reality (AR), embedded in the science subjects, at the level of pre-school education. In this research, a total of 210 parents who have kid(s) studying in the kindergartens have responded to the questionnaire. The Partial Least Square Structural Equation Modelling (PLS-SEM) is employed in this study to analyze the proposed external factors of the adoption of AR technology in the science subjects at the pre-school education. The results show that parents’ attitudes and their awareness of AR technology positively affect their perception of adopting AR technology.